ENTREPRENEURIAL INTENTIONS OF UNDERGRADUATE STUDENTS: MEDIATING ROLE OF PERCEIVED FEASIBILITY - Swandaru, Andono; Harsono, Mugi (JDM (Jurnal Dinamika Manajemen), 2021)
This study aims to test several Krueger models that have not been carried out by Esfandiar. In this model, the variable perceived feasibility is a mediator but Esfandiar did not test the variable so that the feasibility variable was used as a mediator in this research update. Data was collected using an online questionnaire (Google Form) which was given directly to undergraduate students at Sebelas Maret University. The research method used is PLS with questionnaire analysis using WarpPLS version 7.0. The results show that the mediation of feasibility perception plays a partial role in entrepreneurial intentions, meaning that students' perceptions of eligibility will directly influence entrepreneurial desires to become entrepreneurs. When students feel that the entrepreneurial profession is worthy of student perceptions, it will arouse students' entrepreneurial desires. In addition, when students see the entrepreneurial profession as feasible, it will increase students' self-efficacy and collective-efficacy which in turn can generate entrepreneurial desires.